Review of the Draft Fifth National Climate Assessment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Roughly every four years, the U.S. Global Change Research Program produces a congressionally mandated assessment of global change science and the impacts, adaptation, and mitigation of climate change in the United States. The draft Fifth National Climate Assessment (NCA5), released publicly in November 2022, covers a wide range of U.S. impacts, from human health and community well-being to the built environment, businesses and economies, and ecosystems and water resources. NCA5 had the largest scale of collaboration to date in the series, with input from hundreds of experts from all levels of governments, academia, non-government organizations, the private sector, and the public. The National Academies report provides an independent, comprehensive review and makes recommendations to strengthen the accuracy, credibility, and accessibility of the draft NCA5 report. The National Academies’ review of the draft NCA5 report finds that it successfully meets the requirements of the federal mandate, provides accurate information, and effectively communicates climate science to the public, decision makers, and other stakeholders. The review makes recommendations for ways the draft NCA5 report could be strengthened, including: adopting more clear and consistent structure for key messages and figures across the report; resolving inconsistencies between chapters in how terms and topics are discussed, for example the use of scenarios and projections; intentionally applying an equity and justice lens across chapters; and increasing emphasis on certain topical areas.
Keywords: Environment and Environmental Studies; Behavioral and Social Sciences

Disaster Risk Management in an Age of Climate Change: A Summary of the April 3, 2008 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2009)
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies; Conflict and Security Issues

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

A Review of the Draft 2013 National Climate Assessment - National Research Council (The National Academies Press, 2013)
As mandated by the Global Change Research Act (GCRA), the U.S. Global Change Research Program is currently producing a "National Climate Assessment" (NCA). The NCA is a report to inform the President, the Congress, and the American people about the current state of scientific knowledge regarding climate change effects on U.S. regions and key sectors, now and in the coming decades. This document contains an evaluation of the draft NCA report, presented through consensus responses to the Panel's Task Statement questions, and through a large collection of individual Panel member comments and suggestions for specific chapters, statements, figures, etc. While focusing primarily on practical suggestions for immediately improving the current draft, the Panel also raises some broader considerations about fundamental approaches used in certain parts of the NCA report, and about the scope of USGCRP research that underlies the NCA findings. Some suggestions can be viewed as longer-term advice for future versions of NCA work. This NCA has been a significantly more ambitious effort than previous assessments, in terms of the scope of topics addressed and the breadth of public engagement processes involved. Some of the important new areas include the use of "traceable accounts," the articulation of needs for future research and a vision for an ongoing assessment process, the outreach efforts to help various stakeholders define their climate-related information needs, and the initial (though incomplete) effort to assess the current state of climate change response activities around the nation. Given the current state of the science and the scope of resources available, we believe the NCA did a reasonable job of fulfilling its charge overall. Although more needs to be done to fully meet the nation's needs for information and guidance, such needs cannot be met without an expanded research effort on the part of the USGCRP and future assessments. The Panel suggests that the NCA report would be improved by addressing the numerous specific problems and concerns and the more cross-cutting issues raised in the consensus answers to the Task Statement questions—which include, for instance, the need to: 1. provide a clear overarching framework for the report that helps readers understand climate change as part of a complex system with interacting physical, biological, and human social/economic dimensions, and offers practical guidance on using iterative risk management strategies to make decisions in the face of large uncertainties; 2. clearly acknowledge how climate change affects and is affected by other types of major global environmental changes and other societal developments; 3. offer an explicit discussion about the uncertainties associated with the regional model projections presented in the NCA draft; 4. take full advantage of the e-book format planned for this document through strategic use of hyperlinks among different parts of the report and other innovative approaches that help guide the experience of the NCA's diverse audiences. As the nation continues to engage with the threats, opportunities, and surprises of climate change in its many manifestations, the 2013 NCA should prove to be a valuable resource, as a summary of the state of knowledge about climate change and its implications for the American people.
Keywords: Earth Sciences; Behavioral and Social Sciences; Environment and Environmental Studies

Relocation and Other Climate Adaptations on Florida's Gulf Coast: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Strategically moving communities and infrastructure - including homes and businesses - away from environmentally high-risk areas, such as vulnerable coastal regions, has been referred to as managed retreat. Of all the ways humans respond to climate-related hazards, managed retreat has been one of the most controversial due to the difficulty inherent in identifying when, to where, by whom, and the processes by which such movement should take place. To understand and respond to the unique challenges associated with managed retreat, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine sponsored a committee of experts to provide in-depth analysis and identify short- and long-term next steps for Gulf Coast communities that may need to relocate. The committee convened a series of three public workshops in the Gulf Coast region to gather information about on policy and practice considerations, research and data needs, and community engagement strategies. The workshops focused on elevating the voices of communities and individuals contemplating, resisting, undertaking, or facing barriers to relocation (including systemic issues such as structural racism), as well as individuals who have resettled and communities that have received such individuals. Each workshop included community testimonials and panels of local decision makers and experts discussing study-relevant processes and obstacles faced by communities. The first workshop was held in two parts in Houston and Port Arthur, Texas; the second workshop was held in St. Petersburg, Florida; and the third workshop was held in two parts in Thibodaux and Houma, Louisiana. This Proceedings of a Workshop-in Brief recounts the second workshop, held in July 2022 in St. Petersburg, Florida.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Review of the U.S. Global Change Research Program's Draft Decadal Strategic Plan, 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
More intense heat waves, extended wildfire seasons and other escalating impacts of climate change have made it more important than ever to fill knowledge gaps that improve society's understanding, assessment, and response to global change. The US Global Change Research Program (USGCRP) - a collection of 13 Federal entities charged by law to help the United States and the world fill those knowledge gaps - laid out proposed mechanisms and priorities for global change research over the next decade in its draft Decadal Strategic Plan 2022-2031. The draft plan recognizes that priority knowledge gaps have shifted over the past decade as demand has grown for more useful and more inclusive data to inform decision-making, and as the focus on resilience and sustainability has increased. As part of its work in advising the USGCRP since 2011, the National Academies reviewed USGCRP's draft plan to determine how it might be enhanced. Advances in the draft plan include an increased emphasis on social sciences, community engagement with marginalized groups, and promotion of diversity, equity, inclusion, and justice in the production of science. Strengthening the interconnections between the plan's core pillars and expanding opportunities for coordination among federal agencies tasked with responding to global climate change would improve the plan. The draft plan could more strongly convey a sense of urgency throughout the plan and would benefit from additional examples of key research outputs that could advance policy and decision making on global change challenges.
Keywords: Earth Sciences; Behavioral and Social Sciences

Integrating the Human Sciences to Scale Societal Responses to Environmental Change: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Responding to climate change will entail massive socio-emotional and behavioral changes. Translating policies, investments, or built infrastructure-reshaping mandates into real and sustained local impact that incorporates accountability and culture change will require hands-on work. Adaptive societal responses to climate change will succeed or fail based on the attitudes, behaviors, social cohesion and capital, organizational and emotional strengths, and collective impact and input of all stakeholders. To consider how to integrate, align, and converge the broad mix of social, behavioral, and cognitive sciences to produce new insights and inform efforts for enhanced human responses to environmental change, Board on Environmental Change and Society of the National Academies of Sciences, Engineering and Medicine convened this 2023 workshop, entitled Committee on Integrating the Human Sciences to Scale Societal Responses to Environmental Change: A Workshop. The workshop was intended to investigate ways to accelerate and deepen conversations within the social sciences and to focus on synthesis, especially for the purpose of increasing community capacity to understand and effectively respond to climate change-induced environmental changes - at scales ranging from the individual to the household to the community, and all the way up to the level of state and international governance. This publication summarizes the presentations and discussion of the workshop.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Toward a 21st Century National Data Infrastructure: Managing Privacy and Confidentiality Risks with Blended Data - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Protecting privacy and ensuring confidentiality in data is a critical component of modernizing our national data infrastructure. The use of blended data - combining previously collected data sources - presents new considerations for responsible data stewardship. Toward a 21st Century National Data Infrastructure: Managing Privacy and Confidentiality Risks with Blended Data provides a framework for managing disclosure risks that accounts for the unique attributes of blended data and poses a series of questions to guide considered decision-making. Technical approaches to manage disclosure risk have advanced. Recent federal legislation, regulation and guidance has described broadly the roles and responsibilities for stewardship of blended data. The report, drawing from the panel review of both technical and policy approaches, addresses these emerging opportunities and the new challenges and responsibilities they present. The report underscores that trade-offs in disclosure risks, disclosure harms, and data usefulness are unavoidable and are central considerations when planning data-release strategies, particularly for blended data.
Keywords: Behavioral and Social Sciences

Change and the 2020 Census: Not Whether But How - National Research Council (The National Academies Press, 2011)
Sponsored by the Census Bureau and charged to evaluate the 2010 U.S. census with an eye toward suggesting research and development for the 2020 census, the Panel to Review the 2010 Census uses this first interim report to suggest general priorities for 2020 research. Although the Census Bureau has taken some useful organizational and administrative steps to prepare for 2020, the panel offers three core recommendations, and suggests the Census Bureau take and assertive, aggressive approach to 2020 planning rather than casting possibilities purely as hypothetical. The first recommendation on research and development suggests four broad topic areas for research early in the decade. Second, the report suggest that the Bureau take an aggressive, assertive posture toward research in these priority areas. Third, it identifies the setting of bold goals as essential to underscoring the need for serious reengineering and building commitment to change.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Risks and Risk Governance in Shale Gas Development: Summary of Two Workshops - National Research Council (The National Academies Press, 2014)
Natural gas in deep shale formations, which can be developed by hydraulic fracturing and associated technologies (often collectively referred to as "fracking") is dramatically increasing production of natural gas in the United States, where significant gas deposits exist in formations that underlie many states. Major deposits of shale gas exist in many other countries as well. Proponents of shale gas development point to several kinds of benefits, for instance, to local economies and to national "energy independence". Shale gas development has also brought increasing expression of concerns about risks, including to human health, environmental quality, non-energy economic activities in shale regions, and community cohesion. Some of these potential risks are beginning to receive careful evaluation; others are not. Although the risks have not yet been fully characterized or all of them carefully analyzed, governments at all levels are making policy decisions, some of them hard to reverse, about shale gas development and/or how to manage the risks. Risks and Risk Governance in Shale Gas Development is the summary of two workshops convened in May and August 2013 by the National Research Council's Board on Environmental Change and Society to consider and assess claims about the levels and types of risk posed by shale gas development and about the adequacy of existing governance procedures. Participants from engineering, natural, and social scientific communities examined the range of risks and of social and decision-making issues in risk characterization and governance related to gas shale development. Central themes included risk governance in the context of (a) risks that emerge as shale gas development expands, and (b) incomplete or declining regulatory capacity in an era of budgetary stringency. This report summarizes the presentations on risk issues raised in the first workshop, the risk management and governance concepts presented at the second workshop, and the discussions at both workshops.
Keywords: Behavioral and Social Sciences; Energy and Energy Conservation; Environment and Environmental Studies

The Science of Adolescent Risk-Taking: Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Adolescence is a time when youth make decisions, both good and bad, that have consequences for the rest of their lives. Some of these decisions put them at risk of lifelong health problems, injury, or death. The Institute of Medicine held three public workshops between 2008 and 2009 to provide a venue for researchers, health care providers, and community leaders to discuss strategies to improve adolescent health.
Keywords: Behavioral and Social Sciences; Health and Medicine

Accomplishments of the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The U.S. Global Change Research Program (USGCRP) is an interagency program, established by the Global Change Research Act (GCRA) of 1990, mandated by Congress to "assist the Nation and the world to understand, assess, predict, and respond to human-induced and natural processes of global change". Since the USGCRP began, scientific understanding of global change has increased and the information needs of the nation have changed dramatically. A better understanding of what is changing and why can help decision makers in the public and private sectors cope with ongoing change. Accomplishments of the U.S. Global Change Research Program highlights the growth of global change science in the quarter century that the USGCRP has been in existence, and documents some of its contributions to that growth through its primary functions of interagency planning and coordination, and of synthesis of research and practice to inform decision making.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies; Earth Sciences

Lessons Learned from Diverse Efforts to Change Social Norms and Opportunities and Strategies to Promote Behavior Change in Behavioral Health: Proceedings of Two Workshops - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In 2015, the National Academies of Sciences, Engineering, and Medicine convened two workshops with oversight from the Committee on the Science of Changing Behavioral Health Social Norms. The workshops provided input to the committee’s deliberations and contributed to the development of the report Ending Discrimination against People with Mental and Substance Use Disorders. That report was issued to help the Substance Abuse and Mental Health Services Administration and the Office of the Assistant Secretary for Planning and Evaluation, U.S. Department of Health and Human Services, utilize the scientific evidence base in improving public attitudes toward and understanding of behavioral health, specifically in the areas of mental health and substance use disorders. This publication summarizes the presentations and discussions at the two workshops.
Keywords: Behavioral and Social Sciences

Climate and Social Stress: Implications for Security Analysis - National Research Council (The National Academies Press, 2013)
Climate change can reasonably be expected to increase the frequency and intensity of a variety of potentially disruptive environmental events—slowly at first, but then more quickly. It is prudent to expect to be surprised by the way in which these events may cascade, or have far-reaching effects. During the coming decade, certain climate-related events will produce consequences that exceed the capacity of the affected societies or global systems to manage; these may have global security implications. Although focused on events outside the United States, Climate and Social Stress: Implications for Security Analysis recommends a range of research and policy actions to create a whole-of-government approach to increasing understanding of complex and contingent connections between climate and security, and to inform choices about adapting to and reducing vulnerability to climate change.
Keywords: Environment and Environmental Studies; Behavioral and Social Sciences; Earth Sciences; Conflict and Security Issues

Adolescent Risk and Vulnerability: Concepts and Measurement - Institute of Medicine; National Research Council (The National Academies Press, 2001)
Adolescents obviously do not always act in ways that serve their own best interests, even as defined by them. Sometimes their perception of their own risks, even of survival to adulthood, is larger than the reality; in other cases, they underestimate the risks of particular actions or behaviors. It is possible, indeed likely, that some adolescents engage in risky behaviors because of a perception of invulnerability—the current conventional wisdom of adults' views of adolescent behavior. Others, however, take risks because they feel vulnerable to a point approaching hopelessness. In either case, these perceptions can prompt adolescents to make poor decisions that can put them at risk and leave them vulnerable to physical or psychological harm that may have a negative impact on their long-term health and viability. A small planning group was formed to develop a workshop on reconceptualizing adolescent risk and vulnerability. With funding from Carnegie Corporation of New York, the Workshop on Adolescent Risk and Vulnerability: Setting Priorities took place on March 13, 2001, in Washington, DC. The workshop's goal was to put into perspective the total burden of vulnerability that adolescents face, taking advantage of the growing societal concern for adolescents, the need to set priorities for meeting adolescents' needs, and the opportunity to apply decision-making perspectives to this critical area. This report summarizes the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Estimates indicate that as many as 1 in 4 Americans will experience a mental health problem or will misuse alcohol or drugs in their lifetimes. These disorders are among the most highly stigmatized health conditions in the United States, and they remain barriers to full participation in society in areas as basic as education, housing, and employment. Improving the lives of people with mental health and substance abuse disorders has been a priority in the United States for more than 50 years. The Community Mental Health Act of 1963 is considered a major turning point in America's efforts to improve behavioral healthcare. It ushered in an era of optimism and hope and laid the groundwork for the consumer movement and new models of recovery. The consumer movement gave voice to people with mental and substance use disorders and brought their perspectives and experience into national discussions about mental health. However over the same 50-year period, positive change in American public attitudes and beliefs about mental and substance use disorders has lagged behind these advances. Stigma is a complex social phenomenon based on a relationship between an attribute and a stereotype that assigns undesirable labels, qualities, and behaviors to a person with that attribute. Labeled individuals are then socially devalued, which leads to inequality and discrimination. This report contributes to national efforts to understand and change attitudes, beliefs and behaviors that can lead to stigma and discrimination. Changing stigma in a lasting way will require coordinated efforts, which are based on the best possible evidence, supported at the national level with multiyear funding, and planned and implemented by an effective coalition of representative stakeholders. Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change explores stigma and discrimination faced by individuals with mental or substance use disorders and recommends effective strategies for reducing stigma and encouraging people to seek treatment and other supportive services. It offers a set of conclusions and recommendations about successful stigma change strategies and the research needed to inform and evaluate these efforts in the United States.
Keywords: Behavioral and Social Sciences; Health and Medicine

Enhancing Participation in the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. As the understanding of global change has evolved over the past decades and as demand for scientific information on global change has increased, the USGCRP has increasingly focused on research that can inform decisions to cope with current climate variability and change, to reduce the magnitude of future changes, and to prepare for changes projected over coming decades. Overall, the current breadth and depth of research in these agencies is insufficient to meet the country's needs, particularly to support decision makers. This report provides a rationale for evaluating current program membership and capabilities and identifying potential new agencies and departments in the hopes that these changes will enable the program to more effectively inform the public and prepare for the future. It also offers actionable recommendations for adjustments to the methods and procedures that will allow the program to better meet its stated goals.
Keywords: Environment and Environmental Studies; Earth Sciences; Behavioral and Social Sciences

Medical Care Economic Risk: Measuring Financial Vulnerability from Spending on Medical Care - Institute of Medicine; National Research Council (The National Academies Press, 2012)
The United States has seen major advances in medical care during the past decades, but access to care at an affordable cost is not universal. Many Americans lack health care insurance of any kind, and many others with insurance are nonetheless exposed to financial risk because of high premiums, deductibles, co-pays, limits on insurance payments, and uncovered services. One might expect that the U.S. poverty measure would capture these financial effects and trends in them over time. Yet the current official poverty measure developed in the early 1960s does not take into account significant increases and variations in medical care costs, insurance coverage, out-of-pocket spending, and the financial burden imposed on families and individuals. Although medical costs consume a growing share of family and national income and studies regularly document high rates of medical financial stress and debt, the current poverty measure does not capture the consequences for families' economic security or their income available for other basic needs. In 1995, a panel of the National Research Council (NRC) recommended a new poverty measure, which compares families' disposable income to poverty thresholds based on current spending for food, clothing, shelter, utilities, and a little more. The panel's recommendations stimulated extensive collaborative research involving several government agencies on experimental poverty measures that led to a new research Supplemental Poverty Measure (SPM), which the U.S. Census Bureau first published in November 2011 and will update annually. Analyses of the effects of including and excluding certain factors from the new SPM showed that, were it not for the cost that families incurred for premiums and other medical expenses not covered by health insurance, 10 million fewer people would have been poor according to the SPM. The implementation of the patient Protection and Affordable Care Act (ACA) provides a strong impetus to think rigorously about ways to measure medical care economic burden and risk, which is the basis for Medical Care Economic Risk. As new policies - whether part of the ACA or other policies - are implemented that seek to expand and improve health insurance coverage and to protect against the high costs of medical care relative to income, such measures will be important to assess the effects of policy changes in both the short and long term on the extent of financial burden and risk for the population, which are explained in this report.
Keywords: Health and Medicine; Industry and Labor; Behavioral and Social Sciences; Surveys and Statistics

Capturing Change in Science, Technology, and Innovation: Improving Indicators to Inform Policy - National Research Council (The National Academies Press, 2014)
Since the 1950s, under congressional mandate, the U.S. National Science Foundation (NSF) - through its National Center for Science and Engineering Statistics (NCSES) and predecessor agencies - has produced regularly updated measures of research and development expenditures, employment and training in science and engineering, and other indicators of the state of U.S. science and technology. A more recent focus has been on measuring innovation in the corporate sector. NCSES collects its own data on science, technology, and innovation (STI) activities and also incorporates data from other agencies to produce indicators that are used for monitoring purposes - including comparisons among sectors, regions, and with other countries - and for identifying trends that may require policy attention and generate research needs. NCSES also provides extensive tabulations and microdata files for in-depth analysis. Capturing Change in Science, Technology, and Innovation assesses and provides recommendations regarding the need for revised, refocused, and newly developed indicators of STI activities that would enable NCSES to respond to changing policy concerns. This report also identifies and assesses both existing and potential data resources and tools that NCSES could exploit to further develop its indicators program. Finally, the report considers strategic pathways for NCSES to move forward with an improved STI indicators program. The recommendations offered in Capturing Change in Science, Technology, and Innovation are intended to serve as the basis for a strategic program of work that will enhance NCSES's ability to produce indicators that capture change in science, technology, and innovation to inform policy and optimally meet the needs of its user community.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology; Surveys and Statistics

Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Over the last few decades, research, activity, and funding has been devoted to improving the recruitment, retention, and advancement of women in the fields of science, engineering, and medicine. In recent years the diversity of those participating in these fields, particularly the participation of women, has improved and there are significantly more women entering careers and studying science, engineering, and medicine than ever before. However, as women increasingly enter these fields they face biases and barriers and it is not surprising that sexual harassment is one of these barriers. Over thirty years the incidence of sexual harassment in different industries has held steady, yet now more women are in the workforce and in academia, and in the fields of science, engineering, and medicine (as students and faculty) and so more women are experiencing sexual harassment as they work and learn. Over the last several years, revelations of the sexual harassment experienced by women in the workplace and in academic settings have raised urgent questions about the specific impact of this discriminatory behavior on women and the extent to which it is limiting their careers. Sexual Harassment of Women explores the influence of sexual harassment in academia on the career advancement of women in the scientific, technical, and medical workforce. This report reviews the research on the extent to which women in the fields of science, engineering, and medicine are victimized by sexual harassment and examines the existing information on the extent to which sexual harassment in academia negatively impacts the recruitment, retention, and advancement of women pursuing scientific, engineering, technical, and medical careers. It also identifies and analyzes the policies, strategies and practices that have been the most successful in preventing and addressing sexual harassment in these settings.
Keywords: Policy for Science and Technology; Behavioral and Social Sciences